Novel three-dimensional imaging approach for cryoballoon navigation and confirmation of pulmonary vein occlusion - Kowalewski, Christopher; Rodrigo, Miguel; Brodt, Chad; Haddad, Francois; Wang, Paul J.; Narayan, Sanjiv M. (Pace-Pacing and Clinical Electrophysiology, 2020)
Background Cryoballoon apposition is crucial for durable pulmonary vein isolation (PVI) in atrial fibrillation, yet the balloon is difficult to visualize by conventional mapping systems, and pulmonary venography may miss small or out-of-plane leaks. We report a novel imaging system that offers real-time 3D navigation of the cryoballoon within atrial anatomy that may circumvent these issues.
CRIS-Team WoS Importer:2020-03-03